Clinical Implications of Nadir Serum Prostate-Specific Antigen Levels After Transurethral Enucleation of the Prostate - Cheng, Yung-Ting; Hong, Jian-Hua; Lu, Yu-Chuan; Chang, Yi-Kai; Hung, Shih-Chun; Feng, Kuo-Kang; Liu, Shih-Ping; Chow, Po-Ming; Chang, Hong-Chiang; Chen, Chung-Hsin; Pu, Yeong-Shiau (Frontiers in Oncology, 2022)
Objective: Prostate-specific antigen levels after transurethral enucleation of the prostate may serve as indicators of residual cancer foci. To investigate the association between the post-transurethral enucleation of the prostate nadir prostate-specific antigen level and prostate cancer. Materials and Methods: We retrospectively reviewed the data of 428 men who underwent transurethral enucleation of the prostate between March 2015 and April 2021. Based on the following exclusion criterion we excluded 106 men from our analysis: men with metastatic prostate cancer, incomplete transurethral enucleation of the prostate, and missing prostate-specific antigen or prostate size data. Three hundred and twenty-two patients were finally enrolled in our study. These patients were classified into four groups according to the surgical pathology: benign, transition zone (cancer only in the adenoma or transition zone), peripheral zone, and transition and peripheral zone. The optimal cutoff post-transurethral enucleation of the prostate nadir prostate-specific antigen level that predicted residual prostate cancer was determined using receiver operating characteristic curve analysis. Results: In total, 71 (22.0%) men exhibited prostate cancer (median follow, 38.0 months). The benign and combined cancer groups showed similar adenoma removal rates (103.0% and 106.7%, respectively). The median nadir prostate-specific antigen levels after transurethral enucleation of the prostate were 0.76, 0.63, 1.79, and 1.70 ng/ml in the benign, transition zone, peripheral zone, and transition and peripheral zone groups, respectively (p<0.001), with no difference between the benign and transition zone groups (p=0.458); this suggested that complete transurethral enucleation of the prostate removed all cancer nests in the adenoma in the transition zone group. Receiver operating characteristic curve analysis showed that nadir prostate-specific antigen≧1.7 ng/ml predicted residual cancer (area under the curve: 0.787) or cancer with a Gleason score of ≧7 (area under the curve: 0.816) in the remaining prostate. Limitations include the retrospective design and the perioperative peripheral zone biopsy rate. Conclusions: The post-transurethral enucleation of the prostate nadir prostate-specific antigen≧1.7 ng/ml after complete transurethral enucleation of the prostate can predict significant residual cancer. Prostate cancer patients with low post-transurethral enucleation of the prostate prostate-specific antigen levels can be conservatively managed.